Implementing and Testing Risk Preference Induction Mechanisms in Experimental Sealed Bid Auctions - Thomas A. Rietz (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
Risk preference inducing lottery procedures can serve as valuable tools for experimental economists. However, questioning their effectiveness, experimenters may avoid them even when predictions and conclusions depend crucially on risk preferences. Here, I review risk preference induction attempts in sealed bid auctions, discussing factors that promote or hinder success. Making the procedure very transparent and having subjects learn about it in simple environments promote success. Hysteresis resulting from switching between monetary payoffs and lottery procedures in one environment hinder success. Thus, lottery procedures appear sensitive to the implementation. However, implemented carefully, they can generate behavior consistent with the intended preferences.
Keywords: 330